The investigations of a peculiarities of pyrocarbon gas phase densification of powders of the catalytic carbon formations (CCFS), obtained on nickel - Fursov, S.G.; Gujda, V.V.; Lyashenko, S.A.; Meltyukhov, M.V.; Aulova, O.S. (Вопросы атомной науки и техники, 2021)
Investigations on gas-phase densification of the catalytic carbon formations (CCFs), obtained on nickel, using the method of radially driven pyrolysis zone were carried out. Straight dependence of the brittle strength of the CCFs, bonded with pyrocarbon (CCFBPyC), from the CCFs morphology, was shown. It was determined, that the result of decreasing of an amount of fibrous, fine-grained CCFs component is the increasing of strength of the pyrocarbon matrix . For the first time, carbon/carbon composite materials (CCCM ) without cracks, which contain refined or not-refined from nickel, carbon nanomaterials (CNM), were obtained. Досліджене газофазне ущільнення піровуглецем порошків каталітичних утворень вуглецю (КУВ) на Ni за допомогою методу зони піролізу, що радіально рухається. Показана пряма залежність крихкої міцності ущільнених порошків від морфології КУВ. Встановлено, що зменшення кількості дрібнодисперсної волокнистої складової КУВ збільшує міцність піровуглецевої матриці. Вперше отримані вуглець-вуглецеві композиційні матеріали (ВВКМ) без тріщин на основі вуглецевих наноматеріалів (ВНМ) з видаленим та невидаленим нікелем. Исследовано газофазное уплотнение пироуглеродом порошков каталитических образований углерода (КОУ) на Ni методом радиально движущейся зоны пиролиза. Показана прямая зависимость хрупкой прочности уплотненных порошков от морфологии КОУ. Установлено, что уменьшение количества мелкодисперсной волокнистой составляющей КОУ увеличивает прочность пироуглеродной матрицы. Впервые получены углерод-углеродные композиционные материалы (УУКМ) без трещин на основе очищенных и не очищенных от Ni углеродных наноматериалов (УНМ).